Geophysics and The Bible - Robert W. Wiley (LPPM STT Baptis Kalvari, 2022)
There is a misconception that there is disagreement between science and Scriptures. Science is based on facts, not just opinions or preferences. To understand science, we need to consider how science started. It began with people who knew God and who believed that God is a God of order and designs. They believed that the universe He designed would reflect that order and that by studying nature, they could learn more about God and His attributes. Science only deals with nature and not the supernatural or spiritual. When conducting research, scientist use the scientific method to gather measurable empirical evidence in experiments related to a hypothesis, the results of which aim to support or contradict the theory. The basic focus of science is knowledge. It is critical to realize that scientists have not learned everything and that as we gain new knowledge, they must change what they once believed to be true. One example is the understanding of the interior of the Earth. Using earthquake data, scientists originally thought that the Earth had a crust, a mantle, and a solid core. Using earthquake data, they realized that there was also a liquid inner core. More data revealed that the mantle may have different layers. Even with all their tools, scientists have not been able to determine the exact nature of the core, the mantle, or even the crust. Although, we do not yet understand the structure of the core and mantle, scientists have realized that they are essential for life to exist on earth. As scientists have learned more about the mass of the universe and the parameters that control the natural laws of the universe, they have realized that the universe and this planet have been specifically designed to support life here. This has brought many scientists to realize that the universe was specially designed by a Great Engineer.